2012
DOI: 10.1093/dnares/dss008
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Hidden Potential Identity Elements by Computing the Average Discriminating Power of Individual tRNA Positions

Abstract: The recently published discrete mathematical method, extended consensus partition (ECP), identifies nucleotide types at each position that are strictly absent from a given sequence set, while occur in other sets. These are defined as discriminating elements (DEs). In this study using the ECP approach, we mapped potential hidden identity elements that discriminate the 20 different tRNA identities. We filtered the tDNA data set for the obligatory presence of well-established tRNA features, and then separately fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Further tRNA searches in the three domains of life were performed using the Leipzig database ( 164 ) and the archaeal split tRNA databases ( 375 ), and on sequences specific to some phylogenetic groups ( 383 ). First, and as expected, positions in anticodon loops and at the top of the acceptor stems are predicted in Bacteria and Eukarya , with the highest probability in Bacteria ( 388 ). More interesting, positions 30–40 and 31–39 in the anticodon branch are predicted in several tRNAs as determinants, e.g.…”
Section: Expanding the World Of Trna Identitysupporting
confidence: 73%
See 1 more Smart Citation
“…Further tRNA searches in the three domains of life were performed using the Leipzig database ( 164 ) and the archaeal split tRNA databases ( 375 ), and on sequences specific to some phylogenetic groups ( 383 ). First, and as expected, positions in anticodon loops and at the top of the acceptor stems are predicted in Bacteria and Eukarya , with the highest probability in Bacteria ( 388 ). More interesting, positions 30–40 and 31–39 in the anticodon branch are predicted in several tRNAs as determinants, e.g.…”
Section: Expanding the World Of Trna Identitysupporting
confidence: 73%
“…More interesting, positions 30–40 and 31–39 in the anticodon branch are predicted in several tRNAs as determinants, e.g. the pair U 31 –A 39 in E. coli tRNA Trp and S. cerevisiae tRNA Met and the pairs U 30 ·G 40 and G 30 ·U 40 in eukaryal tRNAs Ile and S. cerevisiae tRNA Asp , respectively ( 383 , 388 ). With the exception of pair 30–40 in S. cerevisiae tRNA Asp slightly shifted from the predicted 31–39 pair, these findings are consistent with previous studies using a Bayesian search ( 385 ).…”
Section: Expanding the World Of Trna Identitymentioning
confidence: 99%
“…Other studies showed that the aminoacylation specificity of some tRNA types, among distant species, may be determined by the very same base pair in their acceptor stem. This was demonstrated by both in vivo and in vitro (Giegé et al 1998), as well as computational analysis (Shaul et al 2010;Szenes and Pál 2012). Altogether, these studies suggest that the operational RNA code is common across species in some cases and species-specific in others.…”
Section: Introductionmentioning
confidence: 61%
“…Since AARS do not directly recognize anticodons borne by tRNAs and thus the code, they evolve to dictate the relationship between codons and their corresponding anticodons in rather complex and dynamic ways [17] . Most strikingly, the tRNA pool and the AARS set are rather dynamic and have gone through membership change and recruiting process across taxa [18–25] .…”
Section: Introductionmentioning
confidence: 99%